THU0225 Prevalence of takayasu's arteritis in IZMIR, turkey: A multicenter study. (23rd January 2014) - Kucukyavas, Y.; Aksu, K.; Solmaz, D.; Can, G.; Taylan, A.; Akar, S.; Sari, I.; Birlik, M.; Onen, F.; Akkoc, N.
Abstract : Objectives: Takayasu's Arteritis (TA) is known to be more common in Japanese, Indian and other East and Southeast Asian populations. Unpublished clinical observations indicate that it is relatively common also in Turkey since it is one of the most frequently diagnosed vasculitic disorders in Turkish population. However, until now no studies have examined its frequency in Turkey. Therefore, we have studied its epidemiology in the residents of Izmir. Methods: All rheumatology units at two university and two research and training hospitals in central Izmir were contacted for the review of medical charts of the patients diagnosed as having TA. Electronic search was conducted when computerized health records were available by using the international classification of disease (ICD-10) code for TA (M31-4) and/or the name of the disease. The diagnosis of TA was confirmed by a rheumatologist according to the 1990 American College of Rheumatology (ACR) criteria for TA. The address information obtained from the charts was confirmed by phone calls or follow-up controls. Only Patients from central Izmir were included to the study. The population statistics of central Izmir was obtained from Turkish Statistical Institute, Izmir Branch. Incidence rate was calculated based on the newly diagnosed patients from 2006 to 2010 and the prevalence rate was calculated as point prevalence. Results: Eighty-eight TA patients were detected after the review of medical charts and electronic patient records at university and educational-research hospitals in Izmir. Of these patients, 42 were residents of central Izmir as has been indicated by the review of address records. Based on the population of Central Izmir, minimum prevalence of TA was estimated as 15/million in September 2011 and 14.7/million in December 2010. Over the period from 2006 to 2010, we calculated a minimum incidence rate of 1.0/million (%95 CI 0.5-1.6) in the whole population, and of 0.8/million (%95 CI 0-1.6) in the population below the age of 40. Mean age for onset of symptoms was 33.6±10.8 (13-55) years and female/male ratio was 13/1. Type V and type I were the most frequent types according to angiographic classification, each occurring in about 41% of the patients. Conclusions: TA seems to be relatively common in Turkish population consistent with the previous clinical observations. Disclosure of Interest: None Declared